Species diversity and utilization of bamboo to support lifes the community of Karangwangi Village, Cidaun Sub-District of Cianjur, Indonesia - TIA SETIAWATI; ASEP ZAINAL MUTAQIN; BUDI IRAWAN; AZIFAH ANAMILLAH; JOHAN ISKANDAR (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Setiawati T, Mutaqin AZ, Irawan B, Anâmillah A, Iskandar J. 2017. Species diversity and utilization of bamboo to support lifes the community of Karangwangi Village, Cidaun Sub-District of Cianjur, Indonesia. Biodiversitas 18: 58-64. Bamboo is closely related to the lives of Indonesian people, especially in the rural area. Indonesia has a high diversity of bamboo species with multiple social, economic, cultural and ecological functions. Village communities have taken advantage of bamboo as a building material, furniture, handicrafts, household items, food, and medicine. The objective of this research is to determine the diversity of bamboo species in the Karangwangi Village and their role in supporting the daily life of the local community. The method used in this research is qualitative descriptive analysis method using ethnobotanical approach. Data collection was conducted with a semi-structured interview with local informants, followed by field observation and specimen collection. Bamboo specimens are later morphologically observed and identified.Â  Results of the study showsÂ  that there are 13 species of bamboo in Karangwangi Village, namely Haur Gereng (Bambusa blumeana J.A & J.H. Schult), Haur Geulis (Bambusa sp.), Haur Koneng Â (Bambusa vulgaris var. Striata), Haur Seah (Bambusa vulgaris Schrad Ex. var vittata), Awi Tali (Gigantochloa apus), Awi Hideung (Gigantochloa atroviolacea Widjadja), Awi gombong/Awi Surat (Gigantochloa pseudoarundinacea (Steud.) Widjadja), Awi Temen (Gigantochola atter (Hassk.) Kurz.), Awi Lengka (Gigantochloa hasskarliana (Kurz.) Backer ex Heyne), Awi tamiyang (Schizostachyum iraten Steud.), Awi Gembong(Schizostachyum sp.), Awi Hias (Bambusa glaucophylla Widjadja), and Cangkoreh (Dinochloa scandens (Blume ex Neese) Kuntze). These species are used by the community of Karangwangi Village for various purposes, ranging from building materials, handicrafts, furniture, food, medicine, to fish poison. Keywords: Bamboo, Cianjur, diversity,Â  Karangwangi, utilization